Uji Efektifitas Entomophatogenic Fungi Beauveria bassiana Terhadap Kematian Blattella germananica (L) - Whawan Bayu Arusyid; Lintang Dian Saraswati; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Blattella germanica (L) is an insect vectors and pests. One of controlling effort by using a Entomophatogenic fungi. The study aims to measure the effectiveness of Entomophatogenic fungi Beauveria bassiana against Blattella germanica (L). This research is explanatory laboratories and completely randomized design. Samples Blattella germanica (L) aged 1.5-4 months, 960 tail taken at random from the laboratory. Data analyzing with Probit. The values of Entomophatogenic fungi Beaueria bassiana LC50 is 2,2x106 spores / mL and LC90 was 1,4x109 spores / mL. The values of LT50 of Entomophatogenic fungi Beaueria bassiana is 65,187 hours (±2,7 days) and 267,071 hours (±11 days). Based on this research is known that Entomophatogenic fungi Beauveria bassiana able to kill Blattella germanica (L). Further research needs to be done measuring the amount of germination entomopathogenic fungi Beauveria bassiana againts Blattella germanica (L) at any concentration during the observation time. Advice for health agencies are able to be an alternative vector control on house holds. Suggestions for researchers can be continued research into the use of entomophatogenic fungi against other vector. Advisable for public to be able to innovate pest control with Entomophatogenic fungi Beauveria bassiana againts Blattella germanica (L).